Journal: Kaiser Plant Demolition / Smokestack Demolition at port of Tacoma, Washington - Walt Meglasson (International Society of Explosives Engineers, 2008)
The Kaiser Aluminum Company Smelter, one of several in the Pacific Northwest, was built in 1942 and operated by the Olin Company during World War II and then purchased by Kaiser Aluminum after the war. At its height, the facility employed over 350 workers and was capable of producing 73,000 tons of aluminum per year. It was closed in 2000 through a combination of rising electrical and labor costs, and the inability to compete with more up-to-date foreign facilities.